An overview on the valid publication and typification of Dryoathyrium chinense and Deparia chinensis (Athyriaceae, Aspleniineae, Polypodiales) - Zhang, Jian-Hang; Du, Cheng; Applequist, Wendy L.; Liao, Shuai (Phytotaxa, 2023)
N/A